(3eMGVQGJ hJeGQjf eMdhdI s - (3QHjYI (B, (3UdGMs ((3GdLRGFQ (B:s (3OGQ CLjGd GdQbej (B,s, 2024)
(3jMJhj GdcJGH Ydi eONd YGe dYde GdeMGSHI HeG ajg eaGgje CSGSjI aj GdeMGSHI GdeGdjI cJOabGJ GdMSGH GdeSJfOGJ , GdOhQI GdeMGSHjI, HGdEVGaI Edi GdOaGJQ GdeMGSHjI hGdcTha GdeGdjI h eMGSHI YedjI JCSjS GdeDSSI , OQGSI MSGHGJ GdUfa GdChd , eMGSHI GdQSe Ydi GdbjeI GdeVGaI , ceG jMJhj Ydi eMGSHI GdJKHjJGJ GdeYfhjI hGdYjfjI heMGSHI GdeNRhfGJ cGdTQGA hGdCfJGL hGdHjY, eMGSHI eQOhOGJ GdeTJQjGJ hGdeHjYGJ heMGSHI GdJSHjbGJ Ydi GdeNRhfGJ, eMGSHI GdJNajVGJ GdJLGQjI hGdeGdjI, eMSHI GdCZdaI hGdChQGb GdeGdjI haj GdCNjQ CYeGd fgGjI GdOhQI GdeMGSHjI (B.s
(3HjHdhZQGajG U U(B.287-289s
Keywords: (3GdeMGSHIs; (3GdeMGSHI GdJMdjdjIs; (3GdfXGe GdeMGSHj GdeGdj (B- (3GdLRGFQ s